Ensuring Economic Development And Streamlining Production In A Market Economy - Bekimbetova Malika (Periodica Journal, 2024)
This article explores the interrelationship between economic development and production efficiency in the context of a market economy. It examines the role of innovation, policy reforms, infrastructure development, and workforce training in streamlining production processes and fostering economic growth. Using comparative analysis and case studies, the study highlights best practices from global economies, emphasizing the importance of sustainability and digitalization in achieving long-term competitiveness. Recommendations include adopting advanced technologies, promoting public-private partnerships, and aligning production systems with environmental and social goals. The findings provide actionable insights for policymakers, industry leaders, and researchers.
Keywords: Economic Development; Production Efficiency; Market Economy